2013
DOI: 10.1186/1471-244x-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychiatric disorders and iron deficiency anemia among children and adolescents: a nationwide population-based study

Abstract: BackgroundA great deal of evidence has shown that iron is an important component in cognitive, sensorimotor, and social-emotional development and functioning, because the development of central nervous system processes is highly dependent on iron-containing enzymes and proteins. Deficiency of iron in early life may increase the risk of psychiatric morbidity.MethodsUtilizing the National Health Insurance Database from 1996 to 2008, children and adolescents with a diagnosis of IDA were identified and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 64 publications
10
131
1
4
Order By: Relevance
“…In a study conducted on association between psychiatric disorder and IDA among children and adolescent. In a total of 2957, it was concluded that iron deficiency anemia increased the risk of psychiatric disorders including psychiatric anxiety and depressive disorder [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on association between psychiatric disorder and IDA among children and adolescent. In a total of 2957, it was concluded that iron deficiency anemia increased the risk of psychiatric disorders including psychiatric anxiety and depressive disorder [39]. …”
Section: Discussionmentioning
confidence: 99%
“…The studies with results inconsistent with those obtained in our study had small numbers of samples, with the exception of the study by Bener et al [23] (number of ADHD patients \60, number of healthy control cases \30). A review of the literature shows some studies that have established an association between iron deficiency and psychiatric disorders other than ADHD [52,53]. Therefore, recruiting subjects without comorbid psychiatric disorders in studies assessing the association between ADHD and iron deficiency was considered to be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…About one third of ASD patients suffer from ID, which affects their behavioral phenotype ( Latif et al, 2002 ;Herguner et al, 2012 ). For other disorders (e.g., schizophrenia, bipolar disorder, depression), future research is of vital importance, as data are scarce in these fields ( Chen et al, 2013 ).…”
Section: Neurologic and Psychiatric Manifestations Of Idmentioning
confidence: 99%